(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aims to determine and analyze the relationship between breeders’ knowledge about feed formulations and the conversion value of duck feed. The subjects in this study were Alabio duck breeders in Hambuku Raya Village and Putat Atas Village, Hulu Sungai Utara, South Kalimantan Province, Indonesia with observed objects in the form of Alabio duck feed conversion and breeders’ knowledge of feed formulation knowledge and Alabio duck feed technology. The research method used was non-experimental explorative, the researcher did not give treatment to the group of Alabio ducks and conducted a survey by distributing questionnaires to farmers. Observation of feed conversion is carried out for 3 (three) months from February-April 2018 in each group. Observation of feed conversion is carried out starting from Alabio ducks to produce eggs, which are about 6 months old. Testing of feed conversion, normal data using analysis of variance (Anova), if significant continued with LSD. Survey research is the stage of analyzing using SWOT analysis to determine the level of weakness and strength in the framework of the development of Alabio ducks in the Hulu Sungai Utara Regency of South Kalimantan Province. The results of the analysis of feed conversion of the three groups were not significantly different, the group of Putat Atas Ducks for feed conversion an average of 4.51 ducks Hambuku Raya 1 group an average of feed conversion every month 5.30, the ducks of the Hambuku Raya 2 group the average conversion of feed every month 4.75. SWOT analysis value of weakness factor is 1,764, this factor includes one of them is knowledge of farmers about feed formulation. The results of this study are in line with the results of feed conversion in the first stage of research, the value of feed conversion obtained is still relatively high at 4.51-5.30. The conclusion is the SWOT analysis score of weakness factors one of which is the lack of knowledge of farmers about formulation and feed technology affect the high feed conversion.